The Role of Transformational Leadership in the development of the Performance of School Principals in Bani Ibbid Brigade from Teacher Perspective - Haddad, Mayssoun Tuaimeh Attallah (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the role of transformational leadership in the development of the performance of school principals in Bani Ibbid Brigade from teacher perspective, the researcher used the Descriptive approaches, study Sample consisted from (650) Female and male teacher, chosen stratified randomness manner, to collect data Questioner used, which consisted (32) paragraph, the result of SPSS analysis shown that the degree of the role of transformational leadership in the development of the performance of school principals in Bani Ibbid Brigade from teacher perspective was moderated with average (3.63 out of 5) , The finding also showed there is no statistically significant differences at (α≤0.05) refers to teacher sex (male and female) in addition there were statistically significant differences refers to years of experience in favor of (10 years and more).  Based on the results, the researcher recommended developing the spirit of the cooperative team in the school and supporting participatory development efforts, and the need for principals to pay attention to human relations, and to activate the community partnership between the school and the local community, Holding training courses for managers in modern management methods, and developing teachers professionally and academically, in addition to proposals for complementary studies on the subject.
Keywords: Transformational Leadership; Performance of School Principals; Bani Ibbid Brigade; Teacher